Fear and rumor associated with COVID-19 among Iranian adults, 2020 - Maryam Zamanian; Delniya Ahmadi; Setayesh Sindarreh; Forugh Aleebrahim; Hosein Molavi Vardanjani; Sayed Hassan Faghihi; Roya Safari-Faramani; Maryam Nasirian (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: At time of epidemics, fear and rumors in the community are the main obstacles to the success of prevention programs. AIMS: The aim of the study was to investigate the fear and rumors of coronavirus disease 2019 (COVID-19) among the Iranian population. SETTINGS AND DESIGN: This nationwide cross-sectional study was conducted on residents of six cities of Iran via street-based multistage sampling in March 2020. SUBJECTS AND METHODS: The eligible participants completed a self-administered questionnaire about rumor and fear related to COVID-19 epidemy. STATISTICAL ANALYSIS USED: Data were analyzed through linear regression and survey analysis using Stata (version 11). RESULTS: A total of 2249 (49.3% women) were included. The main source of information was Iranian broadcasting (68.5%). The overall mean (standard deviation) score of fear and rumor among the Iranian population was 15.68 (0.46) and 39.24 (1.27), respectively. Educational level was associated with fear of COVID-19 (P = 0.001). Trusting to the rumors was affected by age (<0.0001), education level (P < 0.0001), underlying disease (P = 0.017), and workplace situation (P < 0.001). CONCLUSIONS: The fear and rumor surrounding the epidemic of COVID-19 were common in society that could make an epidemic of COVID-19 difficult to control. Increasing public awareness via reliable mass media is recommended.